TEACHERS’ STRATEGIES IN TEACHING SPOKEN LANGUAGE TO YOUNG LEARNERS AT CITA HARMONI MONTESSORI SCHOOL - Intan Febyawati; Lungguh Halira Vonti; Entis Sutisna (FKIP UNIVERSITAS PAKUAN, 2021)
Learning foreign language becomes one of the needs that should be trained from an early start. Children from an early age have to be prepared to be ready for it as they will learn to communicate with others. Therefore, in order to assist the children in learning to talk the new language, young learners’ teachers need to create such activities that can improve the students’ ability to speak. However, in the application, the teachers are often questioning what strategies to prepare in order to teach spoken language to young learners. This research aims to investigate the strategies applied by the teachers in teaching spoken language to young learners. Four teachers are involved as participants in this research. This qualitative research uses descriptive analysis design to describe the strategies applied by the teachers at Cita Harmoni Montessori School in teaching spoken language to young learners. Three steps of triangulation are used in this research, they are; classroom observation, interview, and focus group discussion. The findings show that the teachers employ some strategies in order to teach spoken language to young learners who are around four until six years of age. Those strategies are; conversation, talking partner, repetition, gesture, picture, flashcard, song, and video.